Nanofluidic behavior at the interface of sectionalized hydrophobic/hydrophilic patterns in nanochannel. Issue 188 (24th March 2018) - Ye, Ziran; Sun, Guofang; Li, Shunbo; Sui, Chenghua; Yan, Bo; Gao, Fan; Cai, Pinggen; Li, Yun; Chen, Naibo; Wen, Weijia
ABSTRACT: We report a novel method to fabricate sectionalized hydrophobic/hydrophilic nanochannel. Photolithography, dry/wet etching, aligned anodic bonding and selective modification were utilized to fabricate nanochannel with four-sided surface patterns. Nanofluidic behavior was investigated by pressure driven method to study the relationship between pressure and meniscus position. Experimental results showed that evident delay happened to the flow before entering hydrophobic domain, the accumulative pressure required to pass through the hydrophobic section is significantly larger than hydrophilic section. This behavior may be attributed to the influence caused by the underlying wettability variation, especially under large surface-to-volume ratio in nanochannel.